PENDAMPINGAN PELATIHAN APLIKASI MEDIA PEMBELAJARAN POWTOON SISWA SMA DI MASA PANDEMI COVID-19 - Sukiyanto; Choirun Nisa (TAAWUN, 2021)
The purpose of this assistance is to introduce the Powtoon application to high school students so that they have the skills in making online-based learning media during the Covid-19 pandemic. This assistance uses strategies, namely observation, interviews, coordination with the Siman village government, conducting socialization and carrying out training. As for this mentoring activity, the subject is high school students in Siman village. There are approximately 30 high school students living in Siman village. The impact of the changes experienced by the participants after participating in this training was that participants said that before being given this training they had often made learning media using Microsoft Power Points. All participants have never heard or known about the Powtoon learning media application. After holding this training, the participants said that in making the Powtoon learning media application, it was very easy to do because there were many icons and features available that could be used for free, although some were paid, but overall they were not hampered by their creation.